"JITU" STRATEGY (DON'T PANIC, BE CALM AND SWEAT) AS AN EFFECTIVE APPROACH IN HANDLING CHILDREN'S TANTRUM TO SUPPORT SOCIAL DEVELOPMENT - Sholehah Yuliati; Daroe Iswatiningsih (El Midad, 2025)
ABSTRACT Tantrums are a form of emotional expression that is often experienced by early childhood and can interfere with social development if not handled properly. This article discusses the “JITU” strategy (Don’t Panic, Calm, and Rub) as an effective approach in dealing with children’s tantrums. Through a descriptive qualitative method, this study was conducted at ABA Kapas Bojonegoro Kindergarten with observation, interviews, and documentation. The results show that the “JITU” strategy can help parents and teachers respond to tantrums more calmly and empathetically. This approach can create a sense of security for children, build emotional closeness, and support children’s ability to manage emotions and interact socially. Thus, this strategy plays a role in developing positive character. Keywords: tantrums, JITU strategy, social development, early childhood, empathetic approach.